Risk of a false decision on conformity of an environmental compartment due to measurement uncertainty of concentrations of two or more pollutants. (July 2018) - Pennecchi, Francesca R.; Kuselman, Ilya; da Silva, Ricardo J.N.B.; Hibbert, D. Brynn
Abstract: Risks of false decisions in conformity assessment of an environmental compartment due to measurement uncertainty of concentrations of two or more pollutants are discussed. Even if the assessment of conformity for each pollutant in the compartment is successful, the total probability of a false decision concerning the compartment as a whole might still be significant. A model of the total probability of a false decision, formulated on the base of the law of total probability, is used, for example, for a study of test results of total suspended particulate matter (TSPM) concentration in ambient air near to three independent stone quarries located in Israel, as the sources of the air pollution. Total probabilities of underestimation of TSPM concentration (total risk of the inhabitants) and overestimation (total risk of the stone producers) are evaluated as a combination of the particular risks of air conformity assessment concerning TSPM concentration for each quarry. These probabilities characterize conformity of the TSPM concentration in the region of the quarries as a whole. Core code developed in R programming environment for the calculations is provided. Graphical abstract: Image 1 Highlights: Evaluation of total risks of false decisions on conformity of an environmental compartment is developed. The total risks due to measurement uncertainty of concentrations of two or more pollutants are considered. As a case study, the total risks are evaluated at control of total suspended particulate matter (TSPM) concentration in air. The study concerns three independent stone quarries as pollutant sources. The total probabilities of under- and overestimation of TSPM concentration in air are calculated.